Analisis Antara Ekspor, Impor, Nilai Tukar Dan Pertumbuhan Ekonomi di Indonesia - Alfin Rabil Awalam; Alexandra Hukom (An Nafi': Multidisciplinary Science, 2024)
Indonesia, as a developing country with an open economy, relies heavily on international trade and exchange rate stability in an effort to encourage economic growth. Imports and exports are the two main components in foreign trade, while the exchange rate (exchange rate) against other countries' currencies has a vital role in the competition for Indonesian services and products in the international market. Analysis using VECM. Data is obtained through Satu Data Perdagangan, BPS and BI. Research results Imports influence exports, economic growth and exchange rates in the long term. Imports influence exports, exchange rates and economic growth over longer periods of time. The exchange rate influences exports, exchange rates and economic growth over a longer period of time. Economic growth affects imports, exports and exchange rates over a longer period of time.